Inactivated antithrombins as fondaparinux antidotes: a promising alternative to haemostatic agents as assessed in vitro in a thrombin-generation assay - Bourti, Yasmine; Fazavana, Judicael; Armand, Marine; Saller, François; Lasne, Dominique; Borgel, Delphine; Bianchini, Elsa P. (Thrombosis and Haemostasis, 2016)
In the absence of specific antidote to fondaparinux, two modified forms of antithrombin (AT), one recombinant inactive (ri-AT) and the other chemically inactivated (chi-AT), were designed to antagonise AT-mediated anticoagulants, e. g. heparins or fondaparinux. These inactive ATs were previously proven to effectively neutralise anticoagulant activity associated with heparin derivatives in vitro and in vivo, as assessed by direct measurement of anti-FXa activity. This study was undertaken to evaluate in vitro the effectivity of inactive ATs to reverse anticoagulation by heparin derivatives and to compare them with non-specific fondaparinux reversal agents, like recombinant-activated factor VII (rFVIIa) or activated prothrombin-complex concentrate (aPCC), in a thrombin-generation assay (TGA). Addition of fondaparinux (3 μg/ml) to normal plasma inhibited thrombin generation by prolonging lag time (LT) as much as 244 % and lowering endogenous thrombin potential (ETP) to 17 % of their control (normal plasma) values. Fondaparinux-anticoagulant activity was reversed by ri-AT and chi-AT, as reflected by the corrections of LT up to 117 % and 114 % of its control value, and ETP recovery to 78 % and 63 %, respectively. Unlike ri-AT that had no effect on thrombin generation in normal plasma, chi-AT retained anticoagulant activity that minimises its reversal capacity. However, both ATs were more effective than rFVIIa or aPCC at neutralising fondaparinux and, unlike non-specific antidotes, inactive ATs specifically reversed AT-mediated anticoagulant activities, as suggested by their absence of procoagulant activity in anticoagulant-free plasma.
Keywords: Antithrombin; fondaparinux; heparin; reversal; thrombin-generation assay